Régularité et crises du capitalisme ; Les horizons de la crise ; La crise, ses effets sociaux. - Verla, C.; Dupont, M.; Ollivier, F.; Taillandier, A. (Montreuil : PEC, 1987)
Bibliotheek François Vercammen
Frans
Monografie